Improved mitochondrial function in salmon (Salmo salar) following high temperature acclimation suggests that there are cracks in the proverbial ‘ceiling’ - Lucie Gerber; Kathy A. Clow; Felix C. Mark; Anthony K. Gamperl (Scientific Reports, 2020)
Abstract Mitochondrial function can provide key insights into how fish will respond to climate change, due to its important role in heart performance, energy metabolism and oxidative stress. However, whether warm acclimation can maintain or improve the energetic status of the fish heart when exposed to short-term heat stress is not well understood. We acclimated Atlantic salmon, a highly aerobic eurythermal species, to 12 and 20 °C, then measured cardiac mitochondrial functionality and integrity at 20 °C and at 24, 26 and 28 °C (this species’ critical thermal maximum ± 2 °C). Acclimation to 20 °C vs. 12 °C enhanced many aspects of mitochondrial respiratory capacity and efficiency up to 24 °C, and preserved outer mitochondrial membrane integrity up to 26 °C. Further, reactive oxygen species (ROS) production was dramatically decreased at all temperatures. These data suggest that salmon acclimated to ‘normal’ maximum summer temperatures are capable of surviving all but the most extreme ocean heat waves, and that there is no ‘tradeoff’ in heart mitochondrial function when Atlantic salmon are acclimated to high temperatures (i.e., increased oxidative phosphorylation does not result in heightened ROS production). This study suggests that fish species may show quite different acclimatory responses when exposed to prolonged high temperatures, and thus, susceptibility to climate warming.